Incumbency advantages, Prime Minister replacements and government formation - Bäck, Hanna ; 0000-0002-0296-9419; Debus, Marc; Imre, Michael (Party Politics, 2025)
Are incumbent cabinets favored when a new government forms in parliamentary democracies? This article develops and evaluates a new hypothesis on the so-called incumbency advantage in government formation which stresses the role of interpersonal relations in coalition bargaining. We propose that the Prime Minister (PM) plays a particularly important role in bargaining and suggest that when the PM is replaced, the incumbency advantage will be weakened because the familiarity and trust between the bargaining actors is reduced. We evaluate this argument by studying 127 government formation processes in the German States between 1990 and 2023. The findings support our theoretical argument. Governments that form in the German states are more likely to be incumbent cabinets, in particular when there was no PM replacement. Bargaining duration is also significantly shorter when the negotiating parties are the incumbent parties, but this effect is significantly weakened when there was a PM replacement.
Keywords: coalition governments; incumbency advantage; negotiations; political trust; Prime Ministers